A biological study establishing the endotoxin limit of biomaterials for bone regeneration in cranial and femoral implantation of rats. Issue 6 (27th April 2016) - Haishima, Yuji; Hasegawa, Chie; Todoki, Kazuo; Sasaki, Kazuo; Niimi, Shingo; Ozono, Satoru
Abstract: The purpose of this study was to accurately quantify the risk of endotoxin contamination in biomaterials for bone regeneration in order to establish the acceptable endotoxin limit. Collagen sheets containing varying amounts of purified endotoxin from Escherichia coli and dried, heat‐killed E. coli or Staphylococcus aureus cells were implanted into cranial or femoral defects in rats. These defects were artificially prepared to a size of 5 × 5 mm or a diameter of 1 mm, respectively. The degree of osteoanagenesis was assessed by soft X‐ray radiography and histopathology at 1 and 4 weeks after implantation. The collagen sheet containing the dried E. coli cells showed a dose‐dependent delay in cranial and/or femoral osteoanagenesis at endotoxin activities of more than 33.6 EU/mg, at which no inflammatory response was observed. In contrast, no such observation occurred with the collagen sheet containing S. aureus cells. These results suggest that endotoxins may affect the process of osteoanagenesis. Additionally, the no‐observed‐adverse‐effect level was 9.6 EU/mg, corresponding to 255 EU/kg body weight in rats. Interestingly, no delay in osteoanagenesis was induced by the implantation of collagen sheets containing purified endotoxin at any dose tested. This suggested that pure endotoxin implanted into tissues having poor circulation of bodily fluids without bleeding may not be recognized as a foreign substance and may not induce a significant biological response. © 2016 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 105B: 1514–1524, 2017.